The optimal design, synthesis and operation of polygeneration energy systems: Balancing life cycle environmental and economic priorities. (1st September 2021) - Algieri, Angelo; Beraldi, Patrizia; Pagnotta, Giuseppina; Spadafora, Ida
Graphical abstract: Highlights: Integrated design, synthesis, and operation of polygeneration systems are performed. An innovative mixed-integer non-linear programming model is implemented. The multi-objective optimisation accounts for LCA greenhouse gas emissions and costs. Optimised systems provide improvement in primary energy saving and global efficiency. Synergy of thermal storage, traditional and renewable sources gives high flexibility. Abstract: The present study proposes a mathematical approach for the integrated optimal design, synthesis, and operation of polygeneration energy systems with application to the residential sector. The investigated multisource system consists of production photovoltaic modules, gas-fired cogeneration apparatus, auxiliary boilers, absorption chillers, electric chillers, and thermal energy storage units. A mixed-integer non-linear programming model with a bi-objective function, accounting for both the economic and environmental goals computed on a life cycle basis, is formulated. The objective function is defined as a weighted sum of the single objectives, and different solutions are provided to the decision-maker according to the relative importance recognised to the two conflicting purposes. The study, performed for a residential complex in Northern Italy, demonstrates that the effective integration of traditional and renewable sources and the proper operation of thermal storage units increase the system flexibility and sustainability, and overcome the intermittent nature of the solar source. All the suggested optimal polygeneration configurations reduce the total costs (11.2–19.1%) and greenhouse gas emissions (4.7–12.5%) compared to the conventional separate energy production. Furthermore, the optimised multisource energy systems provide primary energy saving (higher than 19.7%), and offer interesting payback periods, with values ranging between 3.8 and 8.1 years.